Community-Based Interventions for Stroke Provided by Nurses and Community Health Workers: A Review of the Literature. Issue 4 (August 2020) - Magwood, Gayenell S.; Nichols, Michelle; Jenkins, Carolyn; Logan, Ayaba; Qanungo, Suparna; Zigbuo-Wenzler, Enia; Ellis, Charles
ABSTRACT: BACKGROUND: Community-based interventions are vital for facilitating poststroke recovery, increasing community participation, and raising awareness about stroke survivors. To optimize recovery and community reintegration, there is a need to understand research findings on community-based interventions that focus on stroke survivors and their caregivers. Although nurses and community health workers (CHWs) are commonly involved in community-based interventions, less is known about their roles relative to other poststroke rehabilitation professionals (physical therapists, occupational therapists, and speech-language pathologists). Thus, the purpose of this review is to explore research focused on improving community-based stroke recovery for adult stroke survivors, caregivers, or both when delivered by nurses or CHWs. METHODS: A systematic review using Scopus, PubMed, EBSCOhost, MEDLINE, CINAHL Complete, and PsycInfo was completed to identify community-based poststroke intervention studies using nurses or CHWs through August 2018. RESULTS: Eighteen studies meeting inclusion criteria from 9 countries were identified. Details regarding nurses' and CHWs' roles were limited or not discussed. Interventions emphasized stroke survivor self-care and caregiver support and were offered face-to-face and in group sessions in the community and home. A wide range of instruments were used to measure outcomes. The results of the interventions provided were mixed. Improvements were observed in perceptions of health, quality of life, knowledge, self-efficacy, self-management, and caregiver support. CONCLUSION: Nurses and CHWs play a pivotal role in community-based care. Evidence suggests community-based interventions facilitate the necessary support for stroke survivors, caregivers, families, and communities to optimize stroke recovery. Data from this review illustrate a continued need for comprehensive programs designed to address the complex needs of stroke survivors and families when they return to their homes and communities.